Source-detector effective solid angle calculation using MCNP6 code - Roos Sophia de Freitas Dam; Alessandra Galvão Menezes dos Santos; William Luna Salgado; César Marques Salgado (Brazilian Journal of Radiation Sciences)
Nuclear techniques based on the attenuation of gamma radiation are used in the industry to calculate flow rate, determine fluid density, predict inorganic scale in oil pipelines, evaluate industrial mixers, among other applications. In order to use these nuclear techniques is necessary to perform studies of important parameters of radioactive source and radiation detectors, which are part of the measurement geometry, such as detection efficiency and solid angle. The aim of this study is to calculate the solid angle and the effective solid angle subtended by a NaI(Tl) detector. The effective solid angle considers attenuation in the medium (between source and detector) and other effects of radiation interaction with matter. Mathematical models were developed using the MCNP6 code in order to evaluate the proposed measurement geometry. The source was placed in different positions to the detector to evaluate frontal and lateral solid angle contributions, which is an important parameter to obtain the intrinsic efficiency response function. The simulated model consists of a NaI(Tl) scintillator detector and two point isotropic sources (241Am and 137Cs). The results for the geometry used in this study showed that the difference between solid angle and effective solid angle reached 20.17% for 241Am and 2.58% for 137Cs, which means that it is highly recommended to consider the effective solid angle in the calculations.